Assessing the governance of human resources for health in Iran: A qualitative study - Fatemeh Manafi; Amir Hossain Takian; Ali Akbari Sari (Wolters Kluwer Medknow Publications, 2019)
BACKGROUND: The main issue for advancing any health system is human resources for health (HRH); although efforts to address HRH shortage and performance have accelerated over recent years, HRH is still a problem for delivering quality services. Addressing key governance issues is essential for developing capable health workforce, and good governance should be an integral part of planning and implementation of HRH. MATERIALS AND METHODS: This is a qualitative study, undertaken in 2017. Data processing included 14 in-depth interviews with the experts of human resource management in medical universities and the Ministry of Health and Medical Education. The sampling was carried out using purposeful sampling method and continued until reaching data saturation. Data analysis was performed using subject analysis method. RESULTS: This study assessment of the human resource governance in ten principles includes strategic vision, participation and consensus orientation, rule of law, transparency, responsiveness, equity and inclusiveness, effectiveness and efficiency, accountability, intelligence and information, and ethics. The result showed that although MOHME tries to reduce insufficient and unbalance's human resources and expand the capacity building in human resource planning, there are not enough practical knowledge and skills among policy-makers. CONCLUSIONS: Strengthening human resource governance should have been among the priorities identified in the health national strategy and government should have a long-term perspective, and all key factors in government, civil society, academia, and other stakeholders should participate in human resource policy-making and their participations should be accepted as a culture.